Purification and properties of dyneins from Paramecium cilia - Travis, Sue M.; Nelson, David L. (Biochimica et biophysica acta, 1988)
Dynein ATPases purified from Paramecium cilia by salt extraction followed by sucrose density gradient centrifugation and anion exchange chromatography. The two major dyneins sedimented in sucrose gradients as species of 22 S and 12 S. After purification by anion exchange chromatography, their specific activities were about 0.4 and 0.5 μmol/min per mg, respectively. The dyneins could be distinguished by subunit composition and immunological crossactivity. Sucrose density gradient centrifugation revealed additional ATPase activity in the region between the 22 S and 12 S dyneins, including a 19 S activity. Mg 2+-ATPase activities of the dyneins and the 19 S activity were inhibited by vanadate and Zn 2+, and were activated by Triton X-100. Antibodies against the 22 S dynein from Paramecium reacted on immunoblots with most of the polypeptides of 22 S dynein, and showed that the heavy chains of 22 S dynein are not indentical to those that sediment at 19 S and 12 S. Several minor ATPase activities were revealed by anion exchange chromatography of fractions from the 22 S, 19 S and 12 S regions of sucrose gradients. These minor activities were stimulated by Mg 2+, inhibited by vanadate, and could be distinguished from each other by their elution positions and polypeptide compositions.